Antibakteri Ekstrak Kulit Buah Kakao (Theobroma cacao) 6,25% dan NaOCl 2,5% Terhadap Bakteri Streptococcus sanguinis - Sepdhyo Wahyu Nugroho; Mandojo Rukmo; Edhie Arief Prasetyo; Tamara Yuanita (Conservative Dentistry Journal, 2019)
Background: Streptococcus sanguinis is a gram-positive bacterium that infects and penetrates into dentinal tubules from a depth of 150 μm up to 792 μm. Chemicals, namely 2.5% NaOCl, are used to mitigate the growth of these bacteria via irrigation of the root canals, but 2.5% NaOCl still has disadvantages including irritating periradicular tissue, having an unpleasant odor, and being toxic. Due to these shortcomings, natural materials are expected to be used as alternatives. Cocoa peel extract has active tannin compounds, flavonoids, alkaloids, terpenoids, and saponins which have antibacterial attributes; a concentration of 6.25% is counted as the minimum bactericidal concentration (MBC) of Streptococcus sanguinis. Aim: To compare the difference of antibacterial power of 6.25% cocoa peel extract (Theobroma cacao) and 2.5% NaOCl against Streptococcus sanguinis. Method: This research is an in vitro experimental laboratory with post-test only control group design. The diffusion method was used on Streptococcus sanguinis planted in tubes containing BHIB, then cultured on petri dishes containing nutrient agar and divided into 3 parts, namely 6.25% cocoa peel extract, 2.5% NaOCl, and negative controls, then each Petri dishes were given a paper disc that had been dripped by 0.01 ml of each ingredient, then incubated in an incubator for 2x24 hours at 37°C; the diameter of the inhibitory zone formed was then observed using a caliper. Results: The average diameter of the inhibition zone formed on 6.25% cocoa peel extract was 19.2000 mm and 2.5% NaOCl was 17.2813 mm against Streptococcus sanguinis. Conclusion: The antibacterial power of 6.25% cocoa peel extract (Theobroma cacao) is higher than 2.5% NaOCl against Streptococcus sanguinis.